Mitochondrial DNA Evaluation and Species Identification of Kemp’s Ridley Sea Turtle (Lepidochelys kempii) Bones After a 3-Year Exposure to Submerged Marine and Terrestrial Environments - Krestoff, Elizabeth S.; Creecy, James P.; Lord, Wayne D.; Haynie, Michelle L.; Coyer, James A.; Sampson, Kate (Frontiers in Marine Science, 2021)
Because Kemp’s ridley sea turtles (Lepidochelys kempii) are critically endangered and are closely related to the vulnerable olive ridleys (L. olivacea), it is forensically and conservationally important to distinguish these species when only skeletal elements remain. Extraction and analysis of DNA sequences is the only method to reliably establish identity, yet are compromised by DNA degradation. To characterize skeletal DNA degradation as a function of time and environment, we placed skeletal elements of a terrestrial mammal (Bos taurus) and L. kempii in a supratidal and subtidal environment for three years. Bi-annual sampling revealed that after 424 days (1.2 yrs), mitochondrial DNA (mtDNA) clearly identified each species from each environment. In the L. kempii supratidal samples, species identification was confirmed after 787 days, however, in subtidal samples, mtDNA quality was inconsistent beyond 424 days and was too degraded for sequencing at 664 days. For the terrestrial mammal, mtDNA reliably identified species from samples exposed to supratidal and subtidal environments after 1511 and 1152 days, respectively. Our results show that mtDNA recovery and identification for Kemp’s ridley sea turtles was reliable up to 1.5 yrs in both environments, but further immersion in seawater significantly degraded nuclear DNA.